Right-Wing Authoritarianism between Different Religions and Its Negative Effect on Attitudes and Behaviors toward COVID-19 Policies in Brazil - Luciano Rossoni; Clayton Pereira Gonçalves; Mônica Pereira da Silva (Socius, 2024)
Some conservative governments denied the COVID-19 pandemic crisis, inducing their supporters to go against sanitary measures. However, could individuals aligned with such political beliefs jeopardize their health due to ideological conviction? In a survey conducted with 1,461 Brazilians exclusively designed for this purpose, the data indicate that the higher the right-wing authoritarianism, the worse the attitudes toward government policies combating COVID-19 and the lower the preventive behavior in the early stages of the pandemic. Considering the support provided by evangelical religions to conservative governments, we compared the effect of right-wing authoritarianism among different religious groups, where the results were consistent. Right-wing authoritarianism emerged as the strongest predictor of resistance to pandemic prevention attitudes and behaviors even when controlling its effect with belief in science, demographics, and risk factors. The implications of the relationship between right-wing authoritarianism and the denial of public health measures have not ceased with the pandemic: Identification with authoritarian agendas points toward resistance to vaccination campaigns and the combating of epidemics.